PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS PERMAINAN TRADISIONAL DALAM MENINGKATKAN MINAT BELAJAR SISWA SD - Tania Linda Rizky; Heru Purnomo (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2021)
Student learning interest really needs to be considered for the academic sustainbility of students. As it is known that students interest in learning can lead to the focus of whether or not students take part in learning. Student focus will also determine the success or failure of students in accepting and understanding the teaching material provided by the teacher. Many teacher and scholls find students wholack interest in learning. So not a few schools have complained about the academic succes achived. And in this study aims to collect and analyze articles that already exit and have discussed related problems as well as succesful efforts to solve a similiar problem related to interest in elementary schools. The criteria for the articles used are those published in 2017-2021. And based on the articles collected, there are results that show that trough observation, anecdotal notes, portfolio, post test show that students’ interest in learning can be increased by adjusting the learning model accordingto the age level of the child, namely by liking to play. And it has been proven by the existence of data which shows that traditional game-based learning models can increase students’ interest and self-quality.